2009
DOI: 10.1038/nm.1955
|View full text |Cite
|
Sign up to set email alerts
|

A shear gradient–dependent platelet aggregation mechanism drives thrombus formation

Abstract: Platelet aggregation at sites of vascular injury is essential for hemostasis and arterial thrombosis. It has long been assumed that platelet aggregation and thrombus growth are initiated by soluble agonists generated at sites of vascular injury. By using high-resolution intravital imaging techniques and hydrodynamic analyses, we show that platelet aggregation is primarily driven by changes in blood flow parameters (rheology), with soluble agonists having a secondary role, stabilizing formed aggregates. We find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

37
707
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 734 publications
(749 citation statements)
references
References 40 publications
37
707
1
4
Order By: Relevance
“…Studies have demonstrated a correlation between spontaneous platelet activation and LV hypertrophy in humans,10, 11 and increased P‐selectin expression has been documented in association both with congestive heart failure and HCM in humans 12, 13, 14. When considering the association of heart disease and platelet activation, an enlarged left atrium, endothelial damage, and the presence of mitral regurgitation all have the potential to generate high shear, resulting in platelet up‐regulation, release of alpha granule components, and increased sensitivity to agonists 15, 16. In vitro studies by Holme et al17 demonstrated shear‐induced platelet activation and development of platelet microparticles under flow conditions that may be similar to those associated with diastolic dysfunction in cats with HCM as suggested by Bedard et al 18…”
mentioning
confidence: 99%
“…Studies have demonstrated a correlation between spontaneous platelet activation and LV hypertrophy in humans,10, 11 and increased P‐selectin expression has been documented in association both with congestive heart failure and HCM in humans 12, 13, 14. When considering the association of heart disease and platelet activation, an enlarged left atrium, endothelial damage, and the presence of mitral regurgitation all have the potential to generate high shear, resulting in platelet up‐regulation, release of alpha granule components, and increased sensitivity to agonists 15, 16. In vitro studies by Holme et al17 demonstrated shear‐induced platelet activation and development of platelet microparticles under flow conditions that may be similar to those associated with diastolic dysfunction in cats with HCM as suggested by Bedard et al 18…”
mentioning
confidence: 99%
“…In this study, we for the first time can clearly demonstrate that DMSO inhibits platelet adherence and platelet aggregation which are essential steps for the physiological and pathophysiological formation of a stable occlusive thrombus [24]. Thrombus formation is the key process in stent thrombosis, a rare but serious complication observed following DES deployment [30,31].…”
Section: Discussionmentioning
confidence: 73%
“…heart beat cycles. The yellow dotted outline shows the geometry of the thrombus recorded with video-microscopy by Nesbitt et al 2 …”
Section: Discussionmentioning
confidence: 99%
“…provided 2 some more insight into the thrombus formation by emphasizing the strong coupling between the biochemical processes and the local hemodynamic properties. According to their experimental work, platelet aggregation is infl uenced by emerging shear forces as platelet adhesion favours low-shear zones.…”
Section: Introductionmentioning
confidence: 99%